The Role of Biologics Agent in the Treatment of Inflammatory Bowel Disease - Tri Hapsoro Guno; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Inflammatory bowel disease (IBD), with major manifestations as Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic intestinal inflammatory disorder with an unknown etiology which pathogensis involving multifactorial immune disorder characterized by chronic relapsing inflammation of the intestine. Management of IBD depends on stage and location of the inflammation consist of the classic conventional treatment and the more new treatment with biologics agent. Biologics agent refers to monoclonal antibodies with activity directed against specific targets involved in the pathogenesis of chronic inflammatory conditions. Advances in the understanding of the specific mechanisms of pathogenesis IBD led to the development of targeted treatment. Today there are six biologics agent approved and used as therapy and there still many other biologics agent on research progress. Many reports show positive report about efficacy for the biological therapy compared with placebo and conventional treatment for the IBD. Limited by their cost and adverse effect that possibly happened, biologics agent is still promising therapy that change the course of IBD treatment.